Proposed media charter for the sports movement in the Arab world - Fawzy Abdel Moneim Dahroug, Mohamed (sports creativity, 2025)
The research problem: There is a problem in the private media has reached a dangerous stage and there is a problem in the state media have become intractable for a solution, and became the sports media party in every policy battles in the Arab world and beyond Anhyazath exceeded logic and reason, even some sports channels switched channels broadcast only events and political news which impact negatively on sports article which offer even make the masses love and encouraging the sport is played for viewing or reading, all this because of the political momentum that we live successive events experienced by the Arab world, and should be sports channels being evaluated because the goal of the sports channel in the first place to provide vision the coverage of the sporting event, and provide lessons to learn them in culture and awareness of sports, but unfortunately did not get to it, and even sports did not become itself a magnet for tourism, as it happens in America, and the sports media system needs re-vocational evaluation, if we're talking about ethics and standards , the people most in need to have a code of honor journalists are athletes. The study aimed to: submit a proposal to the model code of conduct informational media organizations in the Arab world. The researcher used: descriptive method, the researcher also used to gather information for the study, a questionnaire survey of expert opinion. The researcher found the following results for the most important: the consensus of experts gentlemen boil model proposal for a code of conduct for the media movement Sports Arab world, has occupied most of the articles of the Charter of the importance of 100% Kdastantj researcher and acceptance of the proposed model. The most important recommendations came The need to adopt a draft charter Media honor proposed by the sports media institutions in the Arab world, and the creation of a supreme committee oversees the development and implementation of the Charter